2015
DOI: 10.3389/fnana.2015.00059
|View full text |Cite
|
Sign up to set email alerts
|

Long-range projection neurons of the mouse ventral tegmental area: a single-cell axon tracing analysis

Abstract: Pathways arising from the ventral tegmental area (VTA) release dopamine and other neurotransmitters during the expectation and achievement of reward, and are regarded as central links of the brain networks that create drive, pleasure, and addiction. While the global pattern of VTA projections is well-known, the actual axonal wiring of individual VTA neurons had never been investigated. Here, we labeled and analyzed the axons of 30 VTA single neurons by means of single-cell transfection with the Sindbis-pal-eGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
112
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 99 publications
9
112
2
Order By: Relevance
“…As DAergic neurons of this system have different structural and functional features relative to DAergic neurons of the VTA (e.g. different axonal arborization size and pacemaking mechanism) (Aransay et al, 2015; Khaliq and Bean, 2010; Matsuda et al, 2009), a different susceptibility of these neurons to the mutation is plausible. At the light microscopic level, these structures were represented by focal and robust clusters of immunoreactivity for DAT, a plasma membrane protein of DAergic nerve terminals, and for the axonal plasma membrane SNARE SNAP25.…”
Section: Discussionmentioning
confidence: 99%
“…As DAergic neurons of this system have different structural and functional features relative to DAergic neurons of the VTA (e.g. different axonal arborization size and pacemaking mechanism) (Aransay et al, 2015; Khaliq and Bean, 2010; Matsuda et al, 2009), a different susceptibility of these neurons to the mutation is plausible. At the light microscopic level, these structures were represented by focal and robust clusters of immunoreactivity for DAT, a plasma membrane protein of DAergic nerve terminals, and for the axonal plasma membrane SNARE SNAP25.…”
Section: Discussionmentioning
confidence: 99%
“…Our current retrograde studies (not shown), using FluoroGold, indicate that at least some of the dopaminergic fibres originate in the midbrain dopaminergic population of the ventral tegmental area (VTA). Connections between the amygdala and the VTA have been described previously [45][46][47][48][49][50] . The VTA is a key brain area of the reward system [20] and has been linked with social behaviours, including affiliate behaviour and attachment [51] .…”
Section: Discussionmentioning
confidence: 99%
“…Several subdivisions have been identified within the rodent VTA; they include the PBP, PN, rVTA, VTT, and three midline subnuclei: the IF, RLi and CLi (Swanson, 1982; Ikemoto, 2007; Fu et al, 2012; see Aransay et al, 2015 for further discussion). Projections from VTA to Acb compose the so-called mesoaccumbens system in which dopaminergic axons modulate prefrontal, hippocampal and amygdaloid driving inputs at Acb (Brady and O’Donnell, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we used TH double-labeling to quantify the dopaminergic phenotype in mesoaccumbens neurons. Finally, we used the Sindbis-pal-eGFP vector (Furuta et al, 2001; Aransay et al, 2015) to visualize and reconstruct the complete axonal arborization of three mesoaccumbens neurons located in different VTA subdivisions.…”
Section: Introductionmentioning
confidence: 99%